World Politics at the Turn of the 19th Century: The Universal Postal Union and the Influence of the German Empire (KULT_online, 2022)
As part of the debates on globalization and the history of global interdependencies under the concept of ‘global governance,’ Gunnar Wendt’s Das Deutsche Reich und der Weltpostverein attempts to take an unbiased look at German foreign policy in the context of the Universal Postal Union. In reference to historical and political science methods, it represents an important contribution to research on the role of the German Empire as part of the international world economy.